2020
DOI: 10.1016/j.celrep.2020.01.068
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Layered Targeting Mechanism Underlies Nuclear RNA Sorting by the Human Exosome

Abstract: Graphical Abstract Highlights d Most nuclear exosome targeted loci produce NEXT-and PAXT-sensitive RNA isoforms d NEXT targets non-polyadenylated RNA 3 0 ends distributed over kilobase-wide regions d PAXT targets polyadenylated RNA 3 0 ends generated by CPSF at canonical poly(A) sites d NEXT targets are polyadenylated upon NEXT depletion, allowing exosomal decay via PAXT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(138 citation statements)
references
References 60 publications
16
116
0
Order By: Relevance
“…As many of these prematurely terminated transcripts are enriched in both PAXT and NEXT depletions, these transcripts are targeted by the exosome through different mechanisms. As reported previously ( 9 ), the recruitment of PAXT could occur through recognition of pA sites and conventional 3′end processing by the CPA machinery. NEXT could be recruited to these transcripts through its interaction with the CBC ( 62–64 ).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…As many of these prematurely terminated transcripts are enriched in both PAXT and NEXT depletions, these transcripts are targeted by the exosome through different mechanisms. As reported previously ( 9 ), the recruitment of PAXT could occur through recognition of pA sites and conventional 3′end processing by the CPA machinery. NEXT could be recruited to these transcripts through its interaction with the CBC ( 62–64 ).…”
Section: Discussionsupporting
confidence: 66%
“…Exosome-directed decay of nuclear RNA is mediated by adaptor complexes ( 56 ). We therefore investigated which adaptor is implicated in the degradation of transcripts deriving from the four single exoTC classes, focusing on the PAXT connection and the NEXT complex, which primarily target longer polyadenylated and short non-adenylated transcripts, respectively ( 7 , 9 , 14 ). To enable such analysis, we prepared CAGE libraries from cells subjected to siRNA-depletion of ZFC3H1 (PAXT) or ZCCHC8 (NEXT), and plotted the distribution of CAGE exoTC sensitivity scores of siZFC3H1 versus Ctrl and siZCCHC8 versus Ctrl (Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that divergent transcription at TSSs is presumed to occur at most active protein coding genes (5,7,18-21), we expected a large number of PROMPTs in our Zcchc8 knockout cells. Recently, it was shown that the poly(A) exosome-targeting (PAXT) connection can act as a failsafe in the case of NEXT disruption (11). We wondered if NEXT complex redundancy through the PAXT connection would be evident through increased transcription or if the remaining NEXT complex components or RNA exosome were up-regulated as a compensatory mechanism for loss of ZCCHC8 function.…”
Section: Resultsmentioning
confidence: 99%
“…The nuclear exosome targeting complex (NEXT) is responsible for exosomal targeting of PROMPTs, enhancer RNAs (eRNAs), 3’ extended small nuclear RNAs (snRNAs), 3’ extended histone RNAs, and intronic RNAs (9-11). NEXT functions in the nucleoplasm and serves as an adapter complex that facilitates recognition and presentation of RNAs to the nuclear exosome (10-12).…”
Section: Introductionmentioning
confidence: 99%